2021
DOI: 10.3390/ijms22179411
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex CRISPR-Screen Identifies PLA2G4A as Prognostic Marker and Druggable Target for HOXA9 and MEIS1 Dependent AML

Abstract: HOXA9 and MEIS1 are frequently upregulated in acute myeloid leukemia (AML), including those with MLL-rearrangement. Because of their pivotal role in hemostasis, HOXA9 and MEIS1 appear non-druggable. We, thus, interrogated gene expression data of pre-leukemic (overexpressing Hoxa9) and leukemogenic (overexpressing Hoxa9 and Meis1; H9M) murine cell lines to identify cancer vulnerabilities. Through gene expression analysis and gene set enrichment analyses, we compiled a list of 15 candidates for functional valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…Previous study found that the common PLA2G4A upregulation in cancer cells contributes to their migration and invasion and is significantly correlated with unfavorable prognosis (14,15). PLA2G4A overexpression contributed to the malignant phenotype of AML cells together with its partners and is correlated to a poor prognosis in the patients with non-M3/NPM1 wildtype or Hoxa9-and Meis1-dependent AML (16,17). DGKA is the family member of conserved membrane lipid kinases and has been involved in human cancers (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that the common PLA2G4A upregulation in cancer cells contributes to their migration and invasion and is significantly correlated with unfavorable prognosis (14,15). PLA2G4A overexpression contributed to the malignant phenotype of AML cells together with its partners and is correlated to a poor prognosis in the patients with non-M3/NPM1 wildtype or Hoxa9-and Meis1-dependent AML (16,17). DGKA is the family member of conserved membrane lipid kinases and has been involved in human cancers (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic phospholipase A2-α (cPLA2α) encoded by the PLA2G4A gene acts as an upstream regulator of the eicosanoid signaling pathway by providing intracellular AA ( Bazhan and Khaniani, 2018 ). Studies have shown that the PLA2G4A gene can be used as a biomarker in various diseases such as gastric cancer ( Bazhan and Khaniani, 2018 ), acute myeloid leukemia ( Hassan et al, 2021 ; Lai et al, 2021 ), cholangiocarcinoma ( Sun et al, 2019 ), and colorectal cancer ( Zhan et al, 2021a ). PLA2G4A activates the colorectal cancer microenvironment to produce pro-cytokines IL-17A and adenosine, thereby establishing an effective immunosuppressive microenvironment and promoting immune evasion and tumor metastasis ( Zhan et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…1, 524-533. doi:10.1002/ jcb.29258 Yan, H., Xu, J., Xu, Z., Yang, B., Luo, P., and He, Q. (2021). Defining therapeutic targets for renal fibrosis: Exploiting the biology of pathogenesis.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Then, the synergism between Tan I and EADM was tested in HCC cell lines. The Bliss synergy score (SynergyFinder), 29,30 positive excess over bliss additivism (EOBA), 29,31,32 and the drug combination index (CI) 33 were calculated to assess whether Tan I and EADM were synergistic, additive, or antagonistic. These assays allowed us to observe the level of synergy between Tan I and EADM at different dose combinations, while allowing us to visualize the pattern of synergy and predict the dose combination that exhibited the greatest inhibition of proliferation.…”
mentioning
confidence: 99%
“…Furthermore, based on the results of the Bliss synergy score (SynergyFinder), EOBA, and CI, we selected the most reasonable and effective combination concentration as the combined concentration of Tan I and EADM to treat HCC cancer cell lines. [29][30][31][32][33] Synergism between Tan I and EADM was defined as Bliss synergy score (SynergyFinder), 29,30 EOBA, 29,31,32 and CI. 33 The Bliss synergy score was calculated by SynergyFinder, in which 0 means additive, < 0 antagonistic, and > 0 synergistic.…”
mentioning
confidence: 99%